Composite wafer and manufacturing method thereof
The composite wafer design with a silicon layer between oxide or nitride layers addresses weak bonding issues by enhancing low-temperature bonding strength, ensuring robustness and transparency.
Patent Information
- Application Number
- JP2023500760
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-02-19
- Filing Date
- 2022-02-08
- Publication Date
- 2025-01-15
- Estimated Expiration
- 2042-02-08
AI Technical Summary
Existing methods for bonding wafers using plasma activation result in varying bonding strengths, particularly weak bonds between oxides or nitrides at low temperatures, which can peel off due to warping or other issues before sufficient strength is achieved.
A composite wafer structure is created by incorporating a silicon layer between oxide, oxynitride, or nitride layers on the substrates, with a thickness of 2 nm to 250 nm and controlled argon concentration, bonded using plasma activation in specific gas atmospheres.
This approach achieves high bonding strength at low temperatures, preventing peeling and ensuring robust wafer bonds even after heat treatment, while maintaining transparency and low dielectric loss.
Smart Images

Figure 0007614321000001 
Figure 0007614321000002 
Figure 0007614321000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a composite wafer and a method for manufacturing the same. [Background technology]
[0002] One method for bonding two wafers involves treating the surfaces of the wafers to be bonded with plasma, cleaning them as necessary, bonding them together, and then performing low-temperature heat treatment (see Patent Document 1). [Prior art document] [Patent documents] [Patent Document 1] Problems to be solved in Patent No. 6396852
[0003] However, in this plasma activation method, the bonding strength at low temperatures varies greatly depending on the surface material of the wafers to be bonded. In particular, when bonding oxides or nitrides together, the bonding strength at cryogenic temperatures is weak, and there is a problem that the bonding interface peels off due to warping before sufficient strength is achieved.
[0004] In a first aspect of the present invention, a composite wafer is provided, comprising a first substrate having a first layer of any one of an oxide, an oxynitride and a nitride disposed on one side thereof, a second substrate having a second layer of any one of an oxide, an oxynitride and a nitride disposed on one side thereof, and a silicon layer disposed between the first and second layers.
[0005] The silicon layer may be amorphous silicon. The silicon layer may be 2 nm or more and 250 nm or less. The silicon layer may have an argon concentration of 1.5% atomic or less. The silicon layer may have a surface concentration of iron, chromium, and nickel of 5.0e10 atoms / cm 2 It may be the following:
[0006] Each of the first and second substrates may be any one of silicon, glass, alumina, sapphire, lithium tantalate, and lithium niobate. At least one of the first and second layers may be any one of SiO2, SiON, and SiN.
[0007] In a second aspect of the present invention, a method for manufacturing a composite wafer includes the steps of preparing a first substrate having a first layer of any of an oxide, oxynitride and nitride arranged on one side thereof, preparing a second substrate having a second layer of any of an oxide, oxynitride and nitride arranged on one side thereof, forming a silicon layer on one surface of the first layer and the second layer, activating at least one surface of the silicon layer and the other of the first layer and the second layer with plasma, and bonding the first substrate and the second substrate together.
[0008] The silicon layer may be amorphous silicon. In the forming step, the silicon layer may be deposited by PVD or CVD. The silicon layer may be 2 nm to 250 nm. The silicon layer may have an argon concentration of 1.5% atomic or less. The silicon layer may have a surface concentration of iron, chromium, and nickel of 5.0e10 atoms / cm before or after the bonding step. 2 It may be the following:
[0009] Each of the first and second substrates may be made of any one of silicon, glass, alumina, sapphire, lithium tantalate, and lithium niobate. At least one of the first and second layers may be made of any one of SiO2, SiON, and SiN.
[0010] One of the first substrate and the second substrate may have been subjected to ion implantation in advance.The atmosphere for activation by plasma may contain at least one of nitrogen, oxygen, a mixed gas of oxygen and nitrogen, and argon.
[0011] The above summary of the invention does not list all of the features of the present invention. Also, subcombinations of these features may also be inventions. [Brief description of the drawings]
[0012] [Figure 1] This shows the relationship between the material of the surfaces to be bonded and the bonding strength. [Diagram 2] 1 is a schematic cross-sectional view of a composite wafer 10 according to the present embodiment. [Diagram 3] 1 shows schematic diagrams of steps in a method for manufacturing a composite wafer 10. [Figure 4] The optical microscope image shows glass (transparent) and LT bonded together with 160 nm amorphous silicon. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] The present invention will be described below through embodiments of the invention, but the following embodiments do not limit the scope of the invention according to the claims. Furthermore, not all of the combinations of features described in the embodiments are necessarily essential to the solution of the invention.
[0014] First, the present inventors investigated which substances would achieve high bonding strength through surface activation with plasma.
[0015] Figure 1 shows the relationship between the material of the surfaces to be bonded and the bond strength. Activation was performed in a nitrogen atmosphere for about 30 seconds. After bonding, they were treated at 100°C for 24 hours. The bond strength was measured using the blade insertion method (an example of the blade insertion method is "Semiconductor Wafer Bonding - Science and Technology-" Q.-Y. Tong and U. Gosele et al. p.25-28, John Wiley & Sons, Inc. 1999).
[0016] These results show that the bond strength between oxides is relatively weak. It can be seen that the bond strength increases when Si is added. However, although the bond strength of the Si / Si bond was high after heat treatment at 90°C, it peeled off when treated at a higher temperature (250°C). This is thought to be because the moisture trapped at the bond interface had no way to escape, and destroyed the bond when it evaporated.
[0017] The 250℃ treatment was completed without any problems when bonding Si with other materials. Therefore, it was found that high bonding strength can be obtained at low temperatures by bonding Si with either an oxide, an oxynitride, or a nitride. However, it is not always possible to use a silicon wafer as a bonded wafer.
[0018] Therefore, in this embodiment, when the surface of one wafer is an oxide, an oxynitride, or a nitride, a thin Si film is formed on the surface of the other wafer, thereby realizing a Si / oxide (or oxynitride, or nitride) bond.
[0019] 2 is a schematic cross-sectional view of a composite wafer 10 according to this embodiment. The composite wafer 10 includes a first substrate 100, a first layer 200 disposed on one surface of the first substrate 100, a second substrate 500, a second layer 400 disposed on one surface of the second substrate 500, and a silicon layer 300 disposed between the first layer 200 and the second layer 400.
[0020] The first substrate 100 is, for example, any one of silicon, glass, alumina, sapphire, lithium tantalate, and lithium niobate. The first substrate 100 has a thickness of, for example, several hundred μm.
[0021] The first layer 200 is, for example, any one of an oxide, an oxynitride, and a nitride. The first layer 200 is preferably any one of SiO2, SiON, and SiN. The first layer 200 has a thickness of several tens of nm to several μm.
[0022] The second substrate 500 is also made of, for example, any one of silicon, glass, alumina, sapphire, lithium tantalate, and lithium niobate. The material of the second substrate 500 may be the same as or different from the material of the first substrate 100. The second substrate 500 has a thickness of, for example, several hundred μm.
[0023] The second layer 400 is, for example, any one of an oxide, an oxynitride, and a nitride. The second layer 400 is preferably any one of SiO2, SiON, and SiN. The material of the second layer 400 may be the same as or different from the material of the first layer 200. The second layer 400 has a thickness of several tens of nm to several μm.
[0024] The silicon layer 300 is a layer that was originally formed on one or both of the first layer 200 and the second layer 400, and remains between the first layer 200 and the second layer 400 after bonding. The silicon layer 300 is preferably amorphous silicon.
[0025] The silicon layer 300 is preferably 2 nm or more and 250 nm or less. To ensure high transparency in optical applications and to obtain low dielectric loss in high frequency applications, it is preferable to make it thin. If high transparency or low dielectric loss is not required, the silicon layer 300 may be 250 nm or more. On the other hand, if it is too thin, it is easily oxidized and turns into SiO2, so it is preferable for it to have a thickness of several atomic layers or more.
[0026] The concentration of argon contained in the silicon layer 300 is preferably 1.5 atomic % or less. The surface concentrations of iron, chromium and nickel contained in the silicon layer are preferably 5.0e10 atoms / cm 2 It is preferable that the following conditions are satisfied: These conditions can be achieved by performing plasma activated bonding, which will be described later.
[0027] FIG. 3 shows a schematic diagram of the steps in a method for producing the composite wafer 10. As shown in FIG.
[0028] Figure 3 600shows a stage of preparing the first substrate 100. In the example of Fig. 3, the first substrate 100 is shown in a state before the first layer 200 is provided. The first substrate 100 is cut into a plate shape having a thickness of several hundred µm from a LT single crystal ingot formed by, for example, a pulling method.
[0029] Figure 3 601 shows a step of forming a first layer 200 on one surface of a first substrate 100. When the first substrate 100 is LT, the first layer 200 is, for example, SiO2. After the first layer 200 is formed, it is polished to be flattened.
[0030] Figure 3 602 1 shows a step of forming a silicon layer 300 on the bonding surface side of the first layer 200, i.e., the side opposite to the first substrate 100. The silicon layer 300 is amorphous silicon formed by, for example, a PVD method (physical vapor deposition method). A CVD method (chemical vapor deposition method) may be used instead of the PVD method.
[0031] Figure 3 603 3 shows a stage of preparing the second substrate 500. In the example of Fig. 3, the second substrate 500 is shown in a state before the second layer 400 is provided. The second substrate 500 is cut into a plate shape having a thickness of several hundred µm from a silicon single crystal ingot formed by, for example, a pulling method.
[0032] Figure 3 604 shows a step of forming a second layer 400 on one surface of a second substrate 500. When the second substrate 500 is silicon, the second layer 400 is, for example, SiO2. The second layer 400 is, for example, a thermal oxide film obtained by subjecting the second substrate 500 to an oxidation treatment at about 1000°C.
[0033] Figure 3 605shows a step of bonding the first substrate 100 and the second substrate 500 together. Before bonding the first substrate 100 and the second substrate 500 together, at least one of the surfaces to be bonded is activated with plasma. That is, in this embodiment, at least one of the surfaces of the silicon layer 300 and the second layer 400 is activated. The atmosphere for activation with plasma preferably contains at least one of nitrogen, oxygen, a mixed gas of oxygen and nitrogen, and argon.
[0034] The first substrate 100 and the second substrate 500 are bonded to each other at the bonding surface. In this embodiment, the silicon layer 300 and the second layer 400 are bonded to each other. The bonding step may be performed at room temperature.
[0035] In this manner, the composite wafer 10 is manufactured. In this case, a high bonding strength can be obtained by performing a low-temperature heat treatment. In addition to or instead of providing the silicon layer 300 on the first layer 200, the silicon layer 300 may be provided on the second layer 400. Also, ion implantation may be performed in advance on one of the first substrate 100 and the second substrate 500. EXAMPLES
[0036] An LT wafer was prepared by depositing a SiO2 film on it and polishing it. A silicon wafer was prepared on the other side with a thermal oxide film deposited on it. Two types of silicon wafers were prepared: one with an amorphous silicon film of about 10 nm deposited on the thermal oxide film using the PVD method, and one without. Plasma activation was performed in a nitrogen atmosphere for 30 seconds, and the wafers were bonded together and then heat treated at 100°C for 24 hours. This resulted in a composite wafer. The wafer with the amorphous silicon film did not peel off, but the wafer without the film had peeled off around the periphery and cracks were observed. EXAMPLES
[0037] An LT wafer was prepared by depositing a SiO2 film on it and polishing it. A silicon wafer was prepared on the other side with a thermal oxide film deposited. Two types of LT wafers were prepared: one with an amorphous silicon film of about 10 nm deposited on the oxide film by PVD, and one without. Plasma activation was performed in a nitrogen atmosphere for 30 seconds, and after bonding, a heat treatment was performed at 100°C for 24 hours. The wafer with the amorphous silicon film deposited showed no peeling, but the wafer without the film had peeling around the periphery and cracks were observed. EXAMPLES
[0038] A LT wafer was prepared by depositing a SiON film on it and polishing it. A silicon wafer was prepared on the other side with a thermal oxide film deposited on it. Two types of silicon wafers were prepared: one with an amorphous silicon film of about 10 nm deposited on the thermal oxide film by PVD, and one without. Plasma activation was performed in a nitrogen atmosphere for 30 seconds, and after bonding, a heat treatment was performed at 100°C for 24 hours. The wafer with the amorphous silicon film deposited showed no peeling, but the wafer without the film had peeling around the periphery and cracks were observed. EXAMPLES
[0039] An LT wafer was prepared by depositing a SiN film on it and polishing it. A silicon wafer was prepared on the other side with a thermal oxide film deposited on it. Two types of silicon wafers were prepared: one with an amorphous silicon film of about 10 nm deposited on the thermal oxide film by PVD, and one without. Plasma activation was performed in a nitrogen atmosphere for 30 seconds, and after bonding, a heat treatment was performed at 100°C for 24 hours. The wafer with the amorphous silicon film deposited showed no peeling, but the wafer without the film had peeling around the periphery and cracks were observed. EXAMPLES
[0040] The same experiments were carried out in Examples 1 to 4, except that the LT wafer was replaced with LN, alumina (sapphire), and glass. The results were exactly the same as in Examples 1 to 4. EXAMPLES
[0041] Similar experiments were carried out in Examples 1 to 5, except that the atmosphere for plasma activation was changed to oxygen, a mixed gas of oxygen and nitrogen, or argon, and the results were the same. EXAMPLES
[0042] In Examples 1 to 6, similar experiments were carried out using amorphous silicon film formed to a thickness of about 10 nm by CVD, and the results were the same. EXAMPLES
[0043] In Examples 1 to 7, the amorphous silicon was thickened and experiments were performed. The same results were obtained up to a thickness of 250 nm, but when the thickness was increased to 275 nm, minute peeling was observed under an optical microscope over the entire surface of the wafer. As an example, an optical microscope image of glass (transparent) and LT bonded together with 160 nm of amorphous silicon is shown in Figure 4. This is thought to be due to impurities (such as hydrogen) that were incorporated into the amorphous silicon by the PVD or CVD method volatilizing, and the impurities that could not be absorbed induced peeling. Therefore, it can be said that the thickness of the amorphous silicon should be 150 nm or less. EXAMPLES
[0044] One of the wafers to be bonded was previously implanted with hydrogen ions, and the results were the same as in Examples 1 to 8. These wafers were bonded together, heat-treated, and then subjected to ion implantation and delamination to produce a composite wafer with thin films stacked on top of each other. EXAMPLES
[0045] In Examples 1 to 9, plasma activation was performed on only one wafer, not both. Regardless of which wafer was plasma activated, the results were the same as in Examples 1 to 9. 9 It was the same as: EXAMPLES
[0046] A LT wafer that had been implanted with hydrogen ions was prepared by depositing a SiO2 film on it and polishing it. A silicon wafer with a thermal oxide film was prepared on the other side. A PVD method was used to deposit an amorphous silicon film of about 5 nm on the thermal oxide film of the silicon wafer, and an amorphous silicon film of about 5 nm was also deposited on the LT wafer with the SiO2 film. These wafers were bonded together at room temperature using an argon beam under high vacuum. The bonded wafers were peeled off at the ion implantation interface, and a heat treatment at 450°C was performed to restore the crystallinity that had been disturbed by the ion implantation, but some of the wafers peeled off.
[0047] The cross section of this wafer was observed with a transmission electron microscope (TEM), and the amorphous silicon was observed with an energy dispersive X-ray analyzer (EDX), revealing a high concentration of argon (1.5% or more). On the other hand, the sample obtained in Example 9 was also subjected to a heat treatment at 450°C and observed in the same manner, but no argon was observed.
[0048] In addition, metal contamination of silicon wafers irradiated with argon beams used for room temperature bonding was observed using ICP-MS, and iron, chromium, nickel, etc. were found to be 1.0e11atoms / cm 2 High concentrations of metals above 5.0e10 atoms / cm were observed. It can be said that it is essentially difficult to avoid metal contamination in room temperature bonding. On the other hand, no high concentration contamination was observed in the silicon wafers that had been plasma activated, and the contamination level was 5.0e10 atoms / cm for the above metals. 2 The results were as follows.
[0049] Although the present invention has been described above using the embodiments, the technical scope of the present invention is not limited to the scope described in the above embodiments. It is clear to those skilled in the art that various modifications and improvements can be made to the above embodiments. It is clear from the claims that such modifications and improvements can also be included in the technical scope of the present invention.
[0050] It should be noted that the order of execution of each process, such as operations, procedures, steps, and stages, in the devices, systems, programs, and methods shown in the claims, specifications, and drawings is not specifically indicated as "before," "prior to," etc., and may be realized in any order unless the output of a previous process is used in a later process. Even if the operational flow in the claims, specifications, and drawings is explained using "first," "next," etc. for convenience, it does not mean that it is essential to perform the process in this order. [Explanation of symbols]
[0051] 100 First substrate 200 1st layer 300 Silicon Layer 400 2nd layer 500 Second board
Claims
1. Providing a first substrate having a first layer of any one of an oxide, an oxynitride, and a nitride disposed on one surface thereof; providing a second substrate having a second layer of an oxide, an oxynitride, or a nitride disposed on one surface of the second substrate; forming a silicon layer on one surface of the first layer and the second layer; activating a surface of at least one of the silicon layer and the other of the first layer and the second layer with plasma; bonding the first substrate and the second substrate together; Equipped with The plasma-activated atmosphere contains argon, The silicon layer is 2 nm or more and 250 nm or less, A method for producing a composite wafer, wherein the silicon layer has an argon concentration of 1.5 atomic % or less.
2. The method for producing a composite wafer according to claim 1 , wherein the silicon layer is amorphous silicon.
3. 3. The method of claim 2, wherein in the forming step, the silicon layer is formed by PVD or CVD.
4. 2. The method for producing a composite wafer according to claim 1, wherein the surface concentrations of iron, chromium and nickel in the silicon layer before or after the bonding step are 5.0e10 atoms / cm2 or less.
5. 5. The method for producing a composite wafer according to claim 1, wherein each of the first substrate and the second substrate is made of any one of silicon, glass, alumina, sapphire, lithium tantalate, and lithium niobate.
6. The method for producing a composite wafer according to claim 5 , wherein at least one of the first layer and the second layer is made of any one of SiO 2 , SiON, and SiN.
7. 7. The method for producing a composite wafer according to claim 1, wherein one of the first substrate and the second substrate is previously subjected to ion implantation.
8. 8. The method for producing a composite wafer according to claim 1, wherein the atmosphere for activation by plasma contains at least one of nitrogen, oxygen, and a mixed gas of oxygen and nitrogen.
Citation Information
Patent Citations
Manufacture of semiconductor substrate
JP1989230255A
Soi substrate and manufacture therefor
JP1998256263A
Method for manufacturing high-resistivity semiconductor-on-insulator wafers with a charge trap layer
JP2017538297A
Bonded SOI wafer manufacturing method
JP2018137278A
Composite substrate, surface acoustic wave device, and method for manufacturing composite substrate
WO2018088093A1